Myxobolus imparfinis n. sp. (Myxozoa: Myxosporea), a new gill parasite of Imparfinis mirini Haseman (Siluriformes: Heptapteridae) in Brazil - Vieira, Diego Henrique Mirandola Dias [UNESP]; Tagliavini, Vinícius Panciera [UNESP]; Abdallah, Vanessa Doro; de Azevedo, Rodney Kozlowiski (Springer Nature, 2018)
A new species of myxozoan, Myxobolus imparfinis n. sp. is described based on material from the gills of Imparfinis mirini (Haseman) (Heptapteridae). Mature myxospores are round, measuring 7.1–8.4 (7.9 ± 0.3) μm in length, 4.5–6.2 (5.5 ± 0.5) μm in width and 3.1–4.2 (3.7 ± 0.3) μm in thickness. The polar capsules are of unequal size, the larger polar capsule measuring 3.4–4.5 (3.9 ± 0.3) μm in length and 1.4–2.0 (1.7 ± 0.1) μm in width and the smaller capsule measuring 3.1–3.8 (3.4 ± 0.2) μm in length and 1.2–1.8 (1.5 ± 0.2) μm in width. The polar filament presents 6–7 coils. Spores had a prevalence of infection of 75% (6/8). In histological analyses we detected the development site of spores in primary filaments, in afferent branchial artery, thus classifying the type of infection to the filamental type and vascular subtype. The phylogenetic analyses of a dataset including species Myxobolus Bütschli, 1882 and Henneguya Thélohan, 1892 from South America recovered M. imparfinis n. sp. as a sister species of Myxobolus flavus Carriero, Adriano, Silva, Ceccarelli & Maia, 2013. To our knowledge, this is the first record of a myxozoan species parasitising I. mirini.